Three New Approaches to the Drug Trafficking Research Agenda in the 21st Century - Niño, César; Acosta-Cajiao, Clara; González, Camilo (FLACSO - Sede Ecuador, 2020)
Drug trafficking as a subject of study has traditionally been linked to institutional and State-centric perspectives, in which academic production focuses on violence, drug trade, terrorism, armed conflict and drug policy. Based on a literature review and a bibliometric analysis, the objective of this article is to offer three alternative approaches to the research agenda of this phenomenon: the political regime, the paradiplomacy, and the environment. We present three major arguments for debate. In relation to the political regime, drug trafficking expands in contexts of autocratization and consolidates itself in authoritarian regimes. On the other hand, the paradiplomacy of criminal organizations has a low cost, in terms of cooperation, compared to that of the States. Finally, the existence of an environmental degradation problem in the implementation of anti-drug policies is evident. We conclude that these arguments reveal the complexity and the need to approach drug trafficking beyond classical approaches.